Real-time monitoring system for polystyrene coating material deposition onto QCM sensor using ultrasonic atomizer spray. (February 2019) - Rosadi, I; Khusnah, N F; Sakti, S P
Abstract: The polymer coating on a Quartz Crystal Microbalance can be done using spin coating, dipping, spray coating (airbrush) and ultrasonic spray coating. Film thickness and surface morphology of the coating depend on the coating method. Using spray coating, one can control the film thickness and also the morphology by controlling the speed, polymer-solvent particle size, concentration and duration of the deposition process. This paper presents a method for monitoring the deposition of polystyrene onto the QCM sensor by using an ultrasonic atomizer system. The atomizer was working using an ultrasonic generator at 55 kHz. Theoretically, the atomizer was able to produce a mist of solvent and polymer with a diameter of around 28 microns. The system was equipped with a frequency counter which able to monitor the resonance frequency of the sensor being coated in every second with a resolution of 1 Hz. The frequency change was related to the amount of the deposited polymer and solvent on the sensor surface; it means that the deposited polymer can be measured and monitored during the coating process. The deposited polystyrene and its solvent were monitored directly by observing the frequency change of the sensor is coated. For 10 MHz sensor, the resolution was equaled to a deposited mass of 4.2ng. It means that the amount of the coating material to be deposited on the sensor surface can be controlled with high resolution. The evaporation of the solvent after coating process was also able to be monitored directly. The benefit offered by this system besides controlled mass deposited is also the simplicity of the system.